Investigation of Particle Distributions in Xe-Xe Collision at sNN=5.44 TeV with the Tsallis Statistics - Hai-Fu Zhao; Bao-Chun Li; Hong-Wei Dong (Advances in High Energy Physics)
The distribution characteristic of final-state particles is one of the significant parts in high-energy nuclear collisions. The transverse momentum distribution of charged particles carries essential evolution information about the collision system. The Tsallis statistics is used to investigate the transverse momentum distribution of charged particles produced in Xe-Xe collisions at sNN=5.44 TeV. On this basis, we reproduce the nuclear modification factor of the charged particles. The calculated results agree approximately with the experimental data measured by the ALICE Collaboration.